2008
DOI: 10.1029/2008gl035832
|View full text |Cite
|
Sign up to set email alerts
|

Extreme precipitation trends associated with tropical cyclones in the core of the North American monsoon

Abstract: We estimate trends of extreme daily precipitation (P95 > 95th percentile) events in the core of the North American monsoon region in Northwest Mexico during JJAS of 1961–1998. The intensity and seasonal contribution of P95 show significant upward linear trends in the mountain sites, which appear to be related to an increased contribution from heavy precipitation derived from tropical cyclones (TCs). Frequency of P95, total monsoon precipitation, and P95 in coastal stations did not change significantly. TC‐deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 25 publications
(31 reference statements)
4
32
0
2
Order By: Relevance
“…It was investigated if the passage of hurricanes was associated with peaks of daily rainfall in the core region during the two extreme years; however, no clear correlation was found (not shown) possibly because the hurricanes were far away from the impact range (>500 km from the core region). Cavazos et al () documented that the seasonal contribution of extreme daily precipitation (>95th percentile) in the core monsoon region during the wet summer of 1990 was large, and entirely produced by non‐tropical cyclone systems. The rainy season of 1990 was characterized by frequent showers and heavy daily precipitation during the entire monsoon season, while in 2005 most of the rain events occurred from late July to mid‐September.…”
Section: Resultsmentioning
confidence: 99%
“…It was investigated if the passage of hurricanes was associated with peaks of daily rainfall in the core region during the two extreme years; however, no clear correlation was found (not shown) possibly because the hurricanes were far away from the impact range (>500 km from the core region). Cavazos et al () documented that the seasonal contribution of extreme daily precipitation (>95th percentile) in the core monsoon region during the wet summer of 1990 was large, and entirely produced by non‐tropical cyclone systems. The rainy season of 1990 was characterized by frequent showers and heavy daily precipitation during the entire monsoon season, while in 2005 most of the rain events occurred from late July to mid‐September.…”
Section: Resultsmentioning
confidence: 99%
“…In Mexico for example, only few studies have focused on temperature (e.g., Peralta-Hernández et al, 2009;Gutiérrez-Ruacho et al, 2010;García-Cueto et al, 2013;López-Díaz et al, 2013;Cruz-Rico et al, 2015; Alvarez-Olguin and Escalante-Sandoval, 2017) and precipitation (Cavazos et al, 2008;Arriaga-Ramirez and Cavazos, 2010;Martinez-Lopez et al, 2018) trends using station data in some regions of the country. Increases of extreme summer precipitation in the North American monsoon (NAM) region have been associated with the intensification of tropical cyclones (Cavazos et al, 2008;Arriaga-Ramirez and Cavazos, 2010) and the negative phase of the AMO (Curtis, 2008). Englehart and Douglas (2005) and Pavía et al (2009) analysed station data in all Mexico and found a positive temperature trend in the 1970-2000 period, with maximum surface temperature having a stronger positive trend than the minimum temperature.…”
Section: Introductionmentioning
confidence: 99%
“…This has been reported for the southern region of the United States of America and northwestern Mexico (Castro et al, 2001;Cavazos et al, 2008;Cerezo-Mota et al, 2016). The behavior in these patterns of increasing rainfalls has been associated to effects caused by El Niño Southern Oscillation (ENSO) and quality phases of PDO for the region (Pavia et al, 2006).…”
Section: Detection Indicesmentioning
confidence: 73%
“…eventos de lluvia intensa en 1 día y 5 días (RX1day y RX5day) (Figura 2b). Esto se ha reportado para la región de sur de USA y el noroeste de México (Castro et al, 2001;Cavazos et al, 2008;Cerezo-Mota et al, 2016). El comportamiento en estos patrones de aumento de lluvias se ha asociado a efectos de El Niño Oscilación del Sur (ENSO) y fases cálidas de PDO para la región (Pavia et al, 2006 (Figure 2b).…”
Section: Detection Indicesunclassified